Methodological considerations in the determination of projected frontal area in cyclists - Olds, T.; Olive, S. (Journal of Sports Sciences, 1999)
Several studies have reported values for projected frontal area in cycling. Even when similar systems (i.e. riders and bicycles) have been measured, the results have diverged widely. It seems likely that this variability is due to methodological differences. The aims of the present study were to compare three methods of determining the frontal area in cyclists, and to determine the effects on the measured frontal area of variables which contribute to distortion and perspective in photographs. Theoretical models were developed to describe the expected effects of changing the relative position of the cyclist and the reference dimension, the position of the camera relative to the cyclist, and the focal length of the camera. Photographs were then taken of cyclists using different camera positions and settings, and analysed using three different methods: photographic weighing and manual and computerized planimetry. All three methods showed high precision and reliability, and yielded results that were substantially similar (mean values differed by <3.3%). Of possible sources of error, frontal deviation of the reference dimension had the most dramatic effect. Displacing the reference board forward by 0.4 m decreased the measured frontal area by 25%. As the distance between the camera and the cyclist increased, the frontal area decreased by about 5% for each metre. As the focal length of the camera became shorter, the frontal area became smaller, varying by >8% for focal lengths ranging from 28 to 70 mm. These results showed close agreement with the theoretical models, and can be explained in terms of the perspective and distortion effects which occur in photography. The results demonstrate the importance of standardization in measuring the frontal area of cyclists.